Listening Together-Apart: On the Social Mediation of Sound Installation Listening - Robson,N; McPherson,A; Bryan-Kinns,N (2025)
Enacted across the disciplines of sound art and HCI, this paper explores physical behaviours associated with sound installation listening and their mediation by social factors. It presents an ethnomethodological study conducted during the public exhibition of an ultrasonic installation, Being With The Waves. Inaudible to the naked ear, the artwork is heard via custom headphones and, as an experience, manifests differently for individual listeners according to their spatial orientation to speakers, body position, movement, and perceptual behaviour. Arguably, the installation is antisocial by design, foregrounding private rather than collective experience. However, up to six listeners may experience it together, creating a social dimension that inevitably mediates behaviour. An interaction analysis of video observations identifies important ways in which the physical behaviour of listeners appears to be mediated by the presence (or absence) of other people in the exhibition space. The study's findings indicate that the local social dynamic strongly impacts how listeners move and use their bodies, which affects the discovery and exploration of spatial and interactive effects. Critiquing the study from a feminist new materialist perspective, methodological changes are considered that might connect social behaviours with the material design of the installation and foreground situated knowledge.